Pulmonary Embolism in Outpatient Practice: Frequency and Risk Factors - R. M. Aramisova; Z. A. Kambachokova; M. V. Gurizheva; A. M.-G. Kundetova; I. Kh. Gazaeva; A. R. Keysinova; Kh. A. Dombirov; H. Z. Kubaeva; M. Sh. Ediev; A. R. Kolcheva; M. E. Zakharov; K. A. Nahkusheva; et al. (Антибиотики и Химиотерапия, 2022)
The regional features of the frequency of thromboembolic complications and the structure of risk factors in outpatient practice were investigated. Gender and age analysis showed the prevalence of males aged 80 years and older. Cardiac arrhythmias and chronic heart failure had the greatest share in the risk factors for PE.